Blockchain adoption for information sharing: risk decision-making in spacecraft supply chain. Issue 8 (14th September 2021) - Zheng, Kangning; Zhang, Zuopeng (Justin); Chen, Yun; Wu, Jiajin
ABSTRACT: This research studies the risk decision-making (RDM) problem faced by participants in a spacecraft supply chain, considering the adoption of the blockchain technology to facilitate information sharing. We investigate a three-level spacecraft supply chain composed of a spacecraft builder, supplier, and logistics service integrator with the Stackelberg game under the scenarios of decentralized, partially centralized, and fully centralized decision-making. For each scenario, we show how the spacecraft builder's optimal order quantity and the supplier's application degree of the blockchain technology change with the spacecraft builder's risk coefficient. We also compare the overall profit of the supply chain for three decision-making scenarios.